Self-Study Enabling Understanding of the Scholarship of Teaching and Learning: An Exploration of Collaboration among Teacher Educators for Special and Inclusive Education. Issue 2 (4th May 2019) - King, Fiona; Logan, Anna; Lohan, Adrian
ABSTRACT: While teaching is increasingly being accepted as a discipline, there is a growing emphasis on teacher educators researching their own practice to advance the scholarship of teaching and learning (SoTL). This study sought to explore the extent to which self-study contributes to teacher educators' understanding of the SoTL within the discipline of teaching. While self-study is generally accepted as a scholarly approach, the aim here is to address the call in the literature for self-study researchers to evince a commitment to a practice-based and theory-building research agenda by linking with public theories, in this case the SoTL. Additionally, given that self-study is collaborative in nature, findings here may help to address the dearth of knowledge reported in the literature about teacher educator collaboration. A self-study approach was adopted to explore a journey of two teacher educators as they designed, implemented and evaluated new modules in special and inclusive education within an initial teacher education programme in the Republic of Ireland. Analysis and synthesis of data from 24 student teachers and two teacher educators provide insights and understandings into the collaborative interactions and factors that enabled and hindered these interactions. This may support other teacher educators in developing a collaborative pedagogical culture to enhance greater understanding of the SoTL We argue for adopting self-study as a scholarly approach to engage with other theories, such as the SoTL, thus contributing to the broader field of teacher education research.